The ‘Aprendo en casa’ educational strategy and the implementation of the intercultural approach - de la Portilla Díaz, José Manuel (2023)
This research investigates how the intercultural approach was implemented in the educational strategy ‘I learn at home’ during the pandemic caused by COVID-19. In high school students of the San Antonio educational institution in the district of Tanta in the province of Yauyos. Therefore, the article analyzes the perspectives of students, parents, teachers and the school administration regarding their daily activities, adaptation of classes to the local context, priority of customs during the educational strategy ‘I learn at home’, students’ school dropout, and the application of the intercultural approach.